The epigenetic function of androgen receptor in prostate cancer progression - Sawada, Takahiro; Kanemoto, Yoshiaki; Kurokawa, Tomohiro; Kato, Shigeaki (Frontiers in Cell and Developmental Biology, 2023)
Androgen and androgen deprivation (castration) therapies, including androgen receptor antagonists, are clinically used to treat patients with prostate cancer. However, most hormone-dependent prostate cancer patients progress into a malignant state with loss of hormone-dependency, known as castration (drug)-resistant prostate cancer (CRPC), after prolong androgen-based treatments. Even in the CRPC state with irreversible malignancy, androgen receptor (AR) expression is detectable. An epigenetic transition to CRPC induced by the action of AR-mediated androgen could be speculated in the patients with prostate cancer. Androgen receptors belongs to the nuclear receptor superfamily with 48 members in humans, and acts as a ligand-dependent transcriptional factor, leading to local chromatin reorganization for ligand-dependent gene regulation. In this review, we discussed the transcriptional/epigenetic regulatory functions of AR, with emphasis on the clinical applications of AR ligands, AR protein co-regulators, and AR RNA coregulator (enhancer RNA), especially in chromatin reorganization, in patients with prostate cancer.